2019
DOI: 10.1016/j.jaci.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the pleiotropic effects of tissue-resident mast cells

Abstract: Mast cells (MCs), which are best known for their detrimental role in patients with allergic diseases, act in a diverse array of physiologic and pathologic functions made possible by the plurality of MC types. Their various developmental avenues and distinct sensitivity to (micro-) environmental conditions convey extensive heterogeneity, resulting in diverse functions. We briefly summarize this heterogeneity, elaborate on molecular determinants that allow MCs to communicate with their environment to fulfill the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 203 publications
(257 reference statements)
1
43
0
1
Order By: Relevance
“…Different types of MCs have experienced different conditions during differentiation, such as contact with different integrins at their destination tissues or exposure to different cytokines. Important new research reviewed by Huber et al 6 identified transient receptor potential and ORAI Ca 21 channels, essential elements of Ca 21 -dependent MC activation in response to FcεRI clustering, as crucially regulating MC protease content and affecting FcεRI and KIT receptor signaling and responsiveness to IL-4 and other activity-modulating factors in mice. Furthermore, MRGPRX2 was identified as a receptor for secretagogues and small-molecule compounds triggering Ca 21 just 3 years ago.…”
Section: Regulation Of the Pleiotropic Effects Of Tissue-resident Mcsmentioning
confidence: 99%
“…Different types of MCs have experienced different conditions during differentiation, such as contact with different integrins at their destination tissues or exposure to different cytokines. Important new research reviewed by Huber et al 6 identified transient receptor potential and ORAI Ca 21 channels, essential elements of Ca 21 -dependent MC activation in response to FcεRI clustering, as crucially regulating MC protease content and affecting FcεRI and KIT receptor signaling and responsiveness to IL-4 and other activity-modulating factors in mice. Furthermore, MRGPRX2 was identified as a receptor for secretagogues and small-molecule compounds triggering Ca 21 just 3 years ago.…”
Section: Regulation Of the Pleiotropic Effects Of Tissue-resident Mcsmentioning
confidence: 99%
“…A more detailed characterization of the inward current through these channels revealed that it has a ratio of Ca 2+ to Na + permeability (P Ca /P Na ) of 0.55. All seven members of the TRPC subgroup of Transient Receptor Potential (TRP) channel protein family were reported to be expressed in several types of mast cells [for review see (14,22)]. As TRPC channels represent receptor-operated non-selective cation channels that can be activated by stimulation of various G q/11coupled receptors, it can be speculated whether TRPCs might be involved downstream of Mrgprb2 activation by agonists such as compound 48/80.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18]. ТК принимают непосредственное участие в формировании патологических состояний посредством многочисленных компонентов секретома с высокой биологической активностью [20,32,33]. Учитывая известное селективное влияние триптазы ТК на главные патогенетические звенья реализации острого и хронического воспаления, исследование ее биологии в деятельности соединительной ткани кожи при имеющихся трофических нарушениях представляет особое значение в хирургии [7].…”
Section: Introductionunclassified